2021
DOI: 10.1155/2021/6663948
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Epicardial Adipose Tissue Volume Is Associated with High Risk Plaque Profiles in Suspect CAD Patients

Abstract: Objective. To explore the association between EAT volume and plaque precise composition and high risk plaque detected by coronary computed tomography angiography (CCTA). Methods. 101 patients with suspected coronary artery disease (CAD) underwent CCTA examination from March to July 2019 were enrolled, including 70 cases acute coronary syndrome (ACS) and 31 cases stable angina pectoris (SAP). Based on CCTA image, atherosclerotic plaque precise compositions were analyzed using dedicated quantitative software. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Thus, plaque burden in patients with acute coronary syndrome or sudden cardiac death is often higher than that in stable CAD, and the association of PFV with plaque burden may vary depending on the stage of CAD. 11 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, plaque burden in patients with acute coronary syndrome or sudden cardiac death is often higher than that in stable CAD, and the association of PFV with plaque burden may vary depending on the stage of CAD. 11 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, increased PFV was positively correlated with non-calcified plaque burden in patients with acute coronary syndrome but not in stable CAD. 11 The authors have suggested that the effect of pericardial fat deposition on plaque composition may be more than a single mechanism, and PFV may have differential effects on non-calcified plaque depending on the phase of coronary atherosclerosis. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EAT exerts various anti-atherogenic and anti-inflammatory activities and regulates cardiac thermogenesis (8), while PAT apparently has less antiinflammatory activity (9). Disturbances in AT composition and extension associate to adipocytes' hypertrophy, insulin resistance and pro-inflammatory processes (10). According to some studies, the EAT volume is increased in coronary artery disease (CAD) patients (11,12), although this was not confirmed by others (13), and may be a predictor of cardio-metabolic risk (14).…”
Section: Introductionmentioning
confidence: 99%